COST-EFFECTIVENESS ANALYSIS OF THE USE OF METFORMIN AND GLIMEPIRIDE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS INPATIENT AT THE HOSPITAL. ROBERT WOLTER MONGISIDI MANADO CITY - Ni Wayan Meliawati (Sam Ratulangi University, 2023)
Variations in the use of drug therapy (single insulin therapy or insulin combination with OHO) will result in differences in the cost and outcome of the therapy, so a cost-effectiveness analysis of the use of glimepiride and metformin is needed to determine the most cost-effective use of antidiabetic therapy. This study aims to determine which treatment option is more cost-effective between metformin and glimepiride in type 2 diabetes mellitus patients hospitalized at the hospital. Robert Wolter Mongisidi. This research is observational, non-experimental study with descriptive design, where the data taken are retrospective data. The sample in this study were 22 patients consisting of 15 patients taking metformin and 7 patients taking glimepiride. Based on the results of the calculation of the ACER on the use of glimepiride drug therapy with the results of Rp. 73,718 and the use of metformin drug therapy is Rp. 49,156. From the results obtained, it can be concluded that the most cost-effective is metformin with an ACER of Rp. 49,156.